(untitled) (Research, Society and Development, 2022)
The objective is to show the variability of meteorological factors in the area of ​​the Uruçuí Preto river basin - PI, aiming at a contribution to sustainable development in the productive areas of agriculture, grain, fruit, fishing, laser and hydrology. The meteorological factors studied are: temperature (maximum, average and minimum) of the air, and its maximum and minimum fluctuations, thermal amplitude, relative humidity, wind (intensity and direction), total insolation, cloud cover, evaporation, evapotranspiration, precipitation pluvial. The data used are from the 1960-1990 series, acquired by the Superintendence of Northeast Development and by the Technical Assistance and Rural Extension Company of Piauí. The maximum annual temperature is 32.1 °C, its annual minimum is 20.0 °C and the average annual temperature is 26.1 °C. The Köppen climate classification was used, where two climate types are distinguished in the Uruçui Preto River basin – PI, the “Aw” type, hot and humid tropical, with rain in the summer and dry in the winter; and the “Bsh” type, hot semi-arid, with summer rains and dry winters. The variation of the thermal amplitude is from 11.9 to 14.9 ºC. The average relative humidity is 47 to 79%, annual precipitation is 937.7 mm, it was observed that the annual rate of relative humidity follows the annual distribution of precipitation, because precipitation is the process of feeding the natural sources of steam. Of water and moisture. Total insolation in the studied area ranges from 2520 to 2750 hours. The annual evaporation fluctuates from 100 to 226 mm and the annual evapotranspiration fluctuates between 1,160 to 1,600 mm, the annual wind intensity with the following highlights in the area of low wind intensity in the extreme south and in the central and northern part of the southern region is found. If the highest intensities, moderate winds in the northern sector of the central region and throughout the northern region. Annual cloud coverage ranges from 0.4 to 0.6 tenths.